Simultaneous high crystallinity and sub-bandgap optical absorptance in hyperdoped black silicon using nanosecond laser annealing - Franta, B; Pastor, D; Gandhi, HH; Rekemeyer, PH; Gradečak, S; Aziz, MJ; Mazur, E (American Institute of Physics, 2015)
Hyperdoped black silicon fabricated with femtosecond laser irradiation has attracted interest for applications in infrared photodetectors and intermediate band photovoltaics due to its sub-bandgap optical absorptance and light-trapping surface. However, hyperdoped black silicon typically has an amorphous and polyphasic polycrystalline surface that can interfere with carrier transport, electrical rectification, and intermediate band formation. Past studies have used thermal annealing to obtain high crystallinity in hyperdoped black silicon, but thermal annealing causes a deactivation of the sub-bandgap optical absorptance. In this study, nanosecond laser annealing is used to obtain high crystallinity and remove pressure-induced phases in hyperdoped black silicon while maintaining high sub-bandgap optical absorptance and a light-trapping surface morphology. Furthermore, it is shown that nanosecond laser annealing reactivates the sub-bandgap optical absorptance of hyperdoped black silicon after deactivation by thermal annealing. Thermal annealing and nanosecond laser annealing can be combined in sequence to fabricate hyperdoped black silicon that simultaneously shows high crystallinity, high above-bandgap and sub-bandgap absorptance, and a rectifying electrical homojunction. Such nanosecond laser annealing could potentially be applied to non-equilibrium material systems beyond hyperdoped black silicon.